KONSEP DAN MANAJEMEN PENDIDIKAN ISLAM DALAM MEMBINA KEPRIBADIAN ISLAMI DI MA DARUL FURQON JAMPANG TENGAH - Risa Agustini; Siti Nuryanah, Adi Rosadi (Jurnal Salome : Multidisipliner Keilmuan, 2026)
The existing phenomenna is that the character of the participants is currently experiencing a decline, not practicing human values, disrespecting parents, teachers, and fellow friends, learning time is replaced by social media activities. Students are more engrossed in talking on social media and ignoring the real world. This research uses a qualitative research approach with descriptive methods and types of field research. Data collection techniques for interviews, observations and documentation. The data analysis technique is to use data triangulation. This study concluded that the forms of implementation of planning management are swot analysis, conducting discussions, determining the character to be developed, determining activities and creating a development team. The process of implementing planning management is to check the implementation both inside and outside the classroom using discussion, habituation, and example methods. The impact of the implementation process of planning management is an increase in self- awareness in social attitudes in students.